A industrialização do brincar: da interação a solidão - CHAVES, Dayce Kelly Pompeu (2018)
The present research aims to investigate how technologies have influenced the loss of the spontaneous play repertoire and the interaction between children in the contemporary world and how industrialized play has led the children to restricted and solitary environments. We will approach the historical context of the modifications in relation to childhood. play and its importance for the development of children, toys and games over time to the present. The research was the exploratory bibliography for the purpose of appropriation of the main concepts related to the theme and how theorists analyzed the changes in relation to playing. Playing and the greatest cultural asset that children have and the excessive use of technology by children, from a young age has been the concern of educators, parents and medical professionals. It is noticed that the modifications in relation to childhood, play, play, modify with the advances of society, where it starts from a period in which there was no concept of childhood until the modern times, where the electronic equipment interferes in the spontaneous play of contemporary childhood and that is gradually losing space for the industrialized play.